Hepatoprotective effects of Sapium sebiferum in paracetamol-induced liver injury - Liaqat Hussain; Muhammad Sajid Hamid Akash; Madeha Tahir; Kanwal Rehman (Bangladesh Pharmacological Society, 2015)
Sapium sebiferum leaves were used to determine its hepatoprotective effects against paracetamol-induced hepatotoxicity in mice. A dose dependent study was conducted using two different doses (200 mg/kg and 400 mg/kg) of the extract of S. sebiferum against toxic effects of paracetamol (500 mg/kg) in experimental animal model. Silymarin (50 mg/kg) was used as standard drug to compare therapeutic effects of S. sebiferum with control and paracetamol-treated groups. Paracetamol significantly increased the serum levels of liver enzyme markers like alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total bilirubin, and direct bilirubin. The extract showed protective effects by normalizing the liver enzymes markers in a dose dependent manner. Histopathological results confirmed the hepatoprotective effects of leaves of S. sebiferum. We conclude that leaves of S. sebiferum have strong hepatoprotective effects against paracetamol-induced liver injury and can be used in liver injuries caused by drug-induced toxicity.